2003
DOI: 10.1128/jb.185.12.3524-3526.2003
|View full text |Cite
|
Sign up to set email alerts
|

Protein Synthesis in Escherichia coli with Mischarged tRNA

Abstract: Two types of aspartyl-tRNA synthetase exist: the discriminating enzyme (D-AspRS) forms only Asp-tRNA Asp , while the nondiscriminating one (ND-AspRS) also synthesizes Asp-tRNA Asn , a required intermediate in protein synthesis in many organisms (but not in Escherichia coli). On the basis of the E. coli trpA34 missense mutant transformed with heterologous ND-aspS genes, we developed a system with which to measure the in vivo formation of Asp-tRNA Asn and its acceptance by elongation factor EF-Tu. While large am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
49
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(51 citation statements)
references
References 18 publications
(21 reference statements)
2
49
0
Order By: Relevance
“…17) is also more widespread than previously appreciated. The in vivo presence of misacylated aa-tRNA introduces ambiguity into the genetic code and leads to the generation of ''statistical'' proteins (18), whereby the use of misacylated in addition to correctly charged aa-tRNA by the ribosome during translation results in a group of related proteins for any given messenger RNA.…”
mentioning
confidence: 76%
See 1 more Smart Citation
“…17) is also more widespread than previously appreciated. The in vivo presence of misacylated aa-tRNA introduces ambiguity into the genetic code and leads to the generation of ''statistical'' proteins (18), whereby the use of misacylated in addition to correctly charged aa-tRNA by the ribosome during translation results in a group of related proteins for any given messenger RNA.…”
mentioning
confidence: 76%
“…This system was tested in the E. coli trpA34 background (17,38). After transformation with pCBSaspS2, single colonies, streaked on medium B agar plates in the presence or absence of Trp, were incubated at 37°C.…”
mentioning
confidence: 99%
“…At least in some organisms, EF-Tu plays a direct role in preventing Asp-tRNA Asn and Glu-tRNA Gln from entering the ribosome and causing errors in protein biosynthesis (52,29,3), arguing that this toxicity arises from sequestration of tRNA Asn as the abortive Asp-tRNA Asn . However, successful selection experiments in E. coli have relied on Asp-tRNA Asn -mediated incorporation of Asp into proteins at Asn codons, arguing that E. coli EF-Tu binds this misacylated tRNA at least to an extent to be functionally significant (11,33). Thus, it remains to be seen whether the toxicity of Hp ND-AspRS is due to a dearth of Asn-tRNA Asn or to the induction of catastrophic errors arising from low levels of Asp for Asn mutations at a proteome-wide level.…”
Section: Discussionmentioning
confidence: 99%
“…The next step in protein synthesis requires the association of aa-tRNAs with translation factors, and this is used to provide an additional checkpoint. Although EF-Tu discrimination is not absolute (Min et al 2003;Nú ñ ez et al 2004), it can distinguish both precursor noncognate tRNAs (see above) and other incorrectly charged tRNA species ; Asahara and Uhlenbeck 2002), whereas initiation factor 2 specifically binds initiator aa-tRNAs (Mayer et al 2003). Finally, it has been suggested that the ribosome itself might also provide some degree of selectivity towards cognate aa-tRNAs .…”
Section: Beyond Aa-trna Synthesismentioning
confidence: 99%
“…More often, however, the unintended synthesis of noncognate aa-tRNAs presents a threat to the accuracy of translation. Consequently a variety of quality control strategies are employed by the cell to ensure that typically only about one in every 10 4 codons is mistranslated, even though significantly higher rates at particular codons can be tolerated (Ruusala et al 1982;Kurland 1992;Min et al 2003;Nú ñ ez et al 2004). Aside from codon-anticodon pairing (Ogle et al 2003), the mechanisms of translational quality control are broadly of three types; specificity of substrate selection by aa-tRNA synthetases, proofreading, and exclusion from the ribosome.…”
Section: Quality Control and Aa-trnamentioning
confidence: 99%